Perkembangan Serat Batang Rosella (Hibiscus sabdariffa var.Sabdariffa) dengan Perlakuan Naungan dan Volume Penyiraman yang Berbeda - Astuti, Tri; Darmanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2010)
The crop of rosella (Hibiscus sabdariffa var.Sabdariffa) known as medicienal crop and fiber producting crop. Last research was known as pulp. Growth of stem fiber are influenced by environmental factors. The aim of this research is to know the development of stem fiber is treated with different shading and volumes of water sprinkler. Factorial completely randomized design (RCD) was used in this research. The first factor was three levels of shading (I0: 0%, I1: 55%, I2:75%) while the second factor was three levels volumes of watering sprinkler (P1: 240 mL, P2: 480 mL, P3: 720 mL). The observed variable was total, diameter and long of rosella stem fiber cell. Collected data were analysed using Analysis of Variance (ANOVA) followed by Duncan’s Multiply Range Test (DMRT). The result of this research indicate that there are influence interaction shading and volum water sprinkler to rosella stem fiber development. Shading treatment at all volums of water sprinkler have an effect on to improve the length and diameter cell fiber, without shading treatment with volum of water sprinkler at soil field capacity of improve the amount of fiber cell.